Export of Indonesian MSEs and The Role of Partnership - Tambunan, Tulus T. H. (Universitas Airlangga, 2021)
There have been many theoretical and empirical studies on the main factors `determining the ability of micro and small enterprises (MSEs) in developing countries to export. However, so far, there has been very little attention to the role of partnerships between MSEs and large enterprises (LEs), government agencies, banks, or others. The purpose of this study is to fill this gap in the existing literature with the case of MSEs in the manufacturing industry (called micro and small industries or MSIs) in Indonesia. It is a descriptive study that analyses secondary data from a national survey conducted by the Indonesia Central Statistics Agency in 2019. It reveals that the most common form of partnership is marketing partnership. The finding may suggest that MSIs that have partnerships with LEs or others are more able to export than their counterparts without partnerships. Keywords: MSMEs, MSEs, MSIs, PartnershipJEL: M31, L25, D22